Effectiveness of Infrared and William Flexion Exercise on Reducing Pain and Increasing Flexibility in Patients with Low Back Pain - Halimah, Nurul; Pradita, Angria (Babali Publisher, 2023)
Introduction: The condition of low back pain is a musculoskeletal problem without age limit. Patients with lower back pain tend to take analgesic drugs to reduce pain. Apart from pharmacological consumption, the tendency for low back pain sufferers to seek other alternatives, namely; physiotherapy treatment. One of the physiotherapy treatments for low back pain is giving infrared and William flexion exercise or a combination of both. This study aims to determine the effectiveness of infrared and William flexion in reducing pain and flexibility of the lumbar muscles. Method: The research design is quasi experimental pre-posttest with control group. The study population consisted of 44 patients with low back pain at Physiomar Clinic by dividing 40 samples into intervention groups (William flexion exercise) and control group (Infrared and William Flexion Exercise) 2 times/week for 1 month. The pain level measured by using the Visual Analog Scale (VAS) and flexibility using the Modified Schober Test (MST). The data was analyzed by Wilcoxon and Mann Whitney (α≤0.05). Results: This study in intervention group showed a median pre-post pain score of 6.00-5.00 and a median pre-post flexibility value of 3.00-3.00 (p=0.000); while control group showed a median pre-post pain score of 6.00-2.00 and a median pre-post flexibility value of 2.50-10.00 (p=0.000). The combination of infrared and William flexion exercise is better than William flexion exercise for changes in pain and flexibility in low back pain patients at the physiomar clinic